Key factors that influence for seasonal production of Guinea grass - Araujo, Leandro Coelho de [UNESP]; Santos, Patricia Menezes; Rodriguez, Daniel; Macedo Pezzopane, Jose Ricardo (Univ Sao Paolo, 2018)
Climate, soil and management are the main drives for growth and production of tropical pastures. Thus, a better understanding of the effects of these factors and their interactions under climate conditions is required to obtain effective management options. Here, we used data from two field trials to research on climate and management interactions on the production seasonality of Panicum maximum Jacq. Treatments included four sampling times (250, 500, 750, and 1000 degrees C accumulated) during eight regrowth period, under irrigated and rainfed conditions and, cuts were made to simulate grazing intensity. All treatments were arranged in a completely randomized block design with four replications. At each sampling time, basal tillers were sampled to observe meristematic differentiation and were linked with the respective daylength. Soil moisture was determined, and the water availability index (WAI) was calculated. The dry matter production (DMP) was taken and relative productivity was calculated. Soil moisture was the key seasonal drive in spring-summer and the WAI could be used to adjust the maximum production for that season. The major drive for DMP in fall was the daylength, which was found at 11.81 h. For all seasons, DMP correlated better with the residues in early regrowth phase (r = 0.82 and p < 0.0001) and with degree-days at final regrowth phase (r = 0.73 p < 0.01). Applying these critical values to management guidelines should make Guinea grass DMP more efficient on tropical farms.
Keywords: daylength; degree-days; mombaca; tropical forage; water deficit